(untitled) (Fiep Bulletin - online, 2011)
This descriptive cross sectional study had the purpose to assess the subjective sensations of discomfort and pain and the level of physical activity of 18-59 year old administrative workers from public and private companies located in Porto Alegre, RS. The data were collected through the Corlett and Bishop’s diagram and IPAQ short version. The sample was composed of 50 workers, aged between 18 and 47 years old (23 from private companies and 27 from public ones). The data were analyzed through descriptive Statistics, “t”test, and Mann-Whitney non parametric test(? = 0,05). The sample presented low level of physical activity. Female workers´ discomfort and pain were located at the right side of the body, the shoulder, wrist, forearm, leg, feet and ankles segments, neck and also cervical regions (p<0,05).